Depletion of Body and Cerebellar Weights after Chronic Lithium Carbonate Ingestion in Albino Rats (Medical Forum Monthly, 2024)
Objective: The effect of Lithium on the body and brain are well known but enough literature is not available on the effects of Lithium on body and Organ weights. So this study was undertaken to see the effect of Lithium on body and cerebellar weights.Study Design: An experimental study. Place and Duration of Study: This study was conducted at the Anatomy Department BMSI, JPMC, Karachi. Duration of study: April 2012 to June 2012.Materials and Methods: Thirty male albino rats of 200-250 grams were selected and divided into two major groups A and B. Each major group consisted of 15 animals each groups was further divided into three sub-groups according to the time period of the study which was 2 weeks, 6 weeks and 12 weeks. Group A served as control group which was given lab diet and B was the Lithium treated group. Lithium carbonate was given at a dose of 20mg/kg/day for 2, 6 and 12 weeks. Body weights were recorded at the start and of each time period, but cerebellar, Organ weights were recorded at the end of 2nd, 6th and 12th weeks. The body weights and Organ weights are recorded on digital electronic weighing scale.Results: Group B showed a progressive decrease of body and cerebellar weights as the time period of study advanced. But relative cerebellar weights of group B increased with increasing time period of study. Conclusion: The present study concluded that Lithium carbonate causes a significant decrease of body and cerebellar weights.